DAMPAK KERJASAMA SPONSORSHIP PT. MULTISTRADA ARAH SARANA DENGAN MANCESTER UNITED FOOTBALL CLUB TAHUN 2013-2016 - ", Zarina; Yealta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is aimed to explain the the impact of PT. Multistrada Arah Sarana to sponsorship cooperation with Manchester United football club 2013-2016. PT. Multistrada Arah Sarana is an Indonesian tire manufacturer that produces Achilles tires for cars and Corsa for motorcycles. Manchester United is a football club United Kingdom who plays in the highest league of England and is a big club that has big names and many achievements. To increase tire exports to European markets PT. Multisrada Arah Sarana initiative to cooperate with Manchester United Football Club through branding of Achilles and Corsa brand which will become better known after the cooperation also to implement Corporate Social Responsibility (CSR) program. This study was prepared using the perspective of Neoliberalism and the theory of International Cooperation. This research also uses descriptive analysis with qualitative approach. Data collection techniques used are literature studies (library research). The results of this study indicate that sponsorship cooperation is not proven to increase the tire export capacity to the European market. Manchester United's big name is not able to increase the number of tire sales to Europe. But other things have a positive impact is the implementation of United Training as Corporate CSR Porgram that affects a number of children elected in Indonesia to gain knowledge of the activities undertaken by PT. Multisrada Arah Sarana and Manchester United Football Club. Keywords: PT. Multistrada Arah Sarana, Sponsorship, Manchester United Football Club.